A review of the public health management of shigellosis in Australia in the era of culture‐independent diagnostic testing. (23rd October 2016) - Tai, Alex Y.C.; Easton, Marion; Encena, Jess; Rotty, Jessica; Valcanis, Mary; Howden, Benjamin P.; Slota‐Kan, Simon; Gregory, Joy
Abstract: Objective : To review the national case definition for shigellosis following the introduction of culture independent diagnostic testing by clinical laboratories and provide evidence to reform jurisdictional public health practices for the management shigellosis., . Methods : A review of all Australian jurisdictional public health guidelines for shigellosis was conducted. Victorian 2014 shigellosis data were analysed: demographics and risk factors for cases identified by conventional culture or culture‐independent diagnostic methods were described. Results : There was considerable variation in reporting of cases to the National Notifiable Disease Surveillance System (NNDSS) by the eight Australian jurisdictions, with an array of classifications based on diagnostic testing methodologies. Analysis of Victorian 2014 shigellosis data found that culture positive cases were more likely to have reported men who have sex with men (MSM) as a risk factor than PCR positive only cases (p<0.0001) and less likely to have reported overseas travel during their incubation period (p<0.0001). Over a 10‐year period (2005 to 2014), only two of 86 cases who were employed in high‐risk occupations had ongoing positive faecal cultures after appropriate treatment. Conclusions : The national surveillance case definition for shigellosis should be reviewed to facilitate standardised reporting across Australia. All jurisdictions must consider the public health significance of PCR positive only results in their surveillance risk assessments to inform management of shigellosis cases.